(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
In today’s dynamic world, the ability to think creatively is not just a desirable skill but a necessity. Educational systems across the globe are increasingly shifting towards methodologies that promote innovation, adaptability, and interdisciplinary thinking. One such approach is STEAM—an educational model that integrates Science, Technology, Engineering, Arts, and Mathematics into a unified learning paradigm. This article examines the role of STEAM in fostering creative thinking, highlighting its theoretical foundations, practical implementation, and effectiveness in modern classrooms. Through an analysis of current literature and educational practices, we explore how the fusion of analytical and artistic disciplines within STEAM enhances students’ ability to generate original ideas, solve complex problems, and adapt to changing environments. The article also discusses the challenges educators face when implementing STEAM and offers recommendations for maximizing its potential impact on learners’ creativity and overall development.